World-System Analysis: CBAM’s Uneven Impacts on Asia Region’s Steel Exports - Zetthariya, Levynna; Affandi, Roseno Aji (Jurnal Hubungan Internasional, 2025)
The increasing global decarbonization efforts, particularly through the European Union’s Carbon Border Adjustment Mechanism (EU-CBAM), on imported goods have created growing pressure on highly carbon-intensive sectors, such as the steel industry, to adopt greener production methods. This carbon pricing mechanism may constrain the economic growth and development of countries with limited technological, infrastructural, and financial capacities. Existing studies have evaluated CBAM’s effectiveness in achieving its objectives and potential negative consequences through econometric modeling; however, the insights gap regarding steel industries in Southeast Asia and the political power relations of structural inequalities embedded in these transitions remains. This study employed a mixed-method approach, combining comparative qualitative analysis with secondary quantitative data based on World-System Theory (WST) and Global Production Networks (GPN) framework to analyze how CBAM affects China’s, Vietnam’s, and Indonesia’s steel industries based on their structural positions in the world system. The findings revealed that CBAM serves as an instrument of structural domination, reinforcing global inequalities, as non-core countries, including non-EU-oriented exporters, face increasing challenges in adapting to evolving low-carbon standards. To avoid systematic exclusion, the research emphasizes the significance of advancing national climate agendas through the acceleration of domestic emission trading systems (ETS), the development of green technological capabilities, and the enhancement of industrial policies to maintain competitiveness under shifting global market standards.